Fetal microchimerism by mode of delivery: a prospective cohort study. (24th September 2018) - Shree, R; Harrington, WE; Kanaan, SB; Forsyth, A; Cousin, E; Lopez, A; Nelson, JL; Gammill, HS
Abstract : Objective: To compare fetal microchimerism (FMc) in pregnancies with uncomplicated vaginal delivery (VD) versus caesarean delivery (CD). Design: Prospective cohort study. Setting: University of Washington and Fred Hutchinson Cancer Research Center, USA. Population: Women delivering singleton pregnancies without pertinent antenatal complications with uncomplicated deliveries ( n = 36). Methods: We collected maternal predelivery, postdelivery and umbilical cord blood for each mother–baby pair. Following maternal and fetal genotyping, FMc was measured with quantitative polymerase chain reaction assays targeting fetus‐specific polymorphisms. Quantification of FMc is expressed as genome equivalents (gEq) of fetal DNA/100 000 total gEq tested. FMc detection was evaluated by logistic regression while controlling for total number of cell equivalents tested and clinically relevant covariates. FMc concentrations were compared using negative binomial regression while controlling for the same covariates and predelivery FMc positivity. Main outcome measure: Detection and concentration of FMc by mode of delivery. Results: Twenty‐four mother–baby pairs had a VD and 12 had a CD. Postdelivery FMc detection was higher following CD than after VD (58.3% versus 16.7%, P = 0.02). After controlling for covariates, the likelihood of postdelivery FMc detection was almost nine‐fold higher after CD than VD (odds ratio 8.8, 95% CI 1.6–47.6; P = 0.01). With respect to postdelivery FMc concentration, the detection rate ratio for CD versus VD in the adjusted negative binomial regression model was 14.7 (95% CI 3.2–66.8; P = 0.001). Conclusion: Postdelivery peripheral FMc detection and concentration are significantly higher after CD than after VD. As FMc is associated with long‐term maternal health, our findings suggest that the mode of delivery may impact this risk. Tweetable abstract: Greater fetal microchimerism found in maternal blood following caesarean delivery compared with vaginal delivery. Tweetable abstract: Greater fetal microchimerism found in maternal blood following caesarean delivery compared with vaginal delivery.